Between Faith and Fashion: Factors Influencing Muslim Women’s Compliance with Syar’i Hijab Practices - Ahmad Amri; Khomsahrial Romli; Fitri Yanti; Shoni Rahmatullah Amrozi (Journal of Religious Studies, 2026)
The hijab is an Islamic religious obligation clearly stipulated in the Qur’an and Hadith. This study aims to describe the practice of wearing the hijab in accordance with Islamic law and to identify the factors influencing this practice. The research method employed is a descriptive-analytical qualitative approach, with data collected through semi-structured interviews, observation, and a literature review. The results indicate that hijab compliance with Islamic law must meet the criteria of fully covering the aurat, being loose-fitting, non-transparent, and not conspicuous. Internal factors such as religious understanding, self-awareness, and spiritual motivation, as well as external factors such as family influence, social environment, and media, also influence an individual’s decision to wear the hijab. Major challenges in hijab implementation include social stigma, cultural pressure, and a lack of education regarding Sharia-compliant hijab. Therefore, comprehensive educational and outreach efforts are needed to support the practice of wearing the hijab in accordance with Sharia.